Geological engineering - González de Vallejo, Luis I., (CRC Press/Balkema, 2011)
"Interpreting a geological setting for the purposes of engineering design and construction requires knowledge of geological engineering and engineering geology, leading to integrated engineering solutions which take into account both ground conditions and environment. This textbook, extensively illustrated, covers the subject area of geological engineering in four sections: 1. Fundamentals: soil mechanics, rock mechanics and hydrogeology; 2. Methods: site investigations, rock mass characterization and engineering geology mapping; 3. Applications: foundations, slope stability, tunnelling, dams, reservoirs and earth works, and 4. Geohazards: landslides, earthquake hazards and prevention and mitigation of geological hazards. The book can serve as a basic reference work for practising engineering geologists, geological and geotechnical engineers, geologists, civil and mining engineers and those professionals involved in design and construction of foundations, tunneling, earth works and excavations for infrastructures, buildings, mining operations, etc. As a textbook it develops an extensive teaching programme of geological engineering and is designed for undergraduate and postgraduate students and academics. Covering basic concepts up to the newest methodologies and procedures used in geological engineering. The book is illustrated with many educational working examples and graphical materials"--Provided by publisher.